2022
DOI: 10.1097/jnn.0000000000000651
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stroke Survivors' Physical Disability on the Presence of Caregiver Burden: A Systematic Review

Abstract: BACKGROUND: Caregiver burden associated with caring for stroke survivors remains a prominent issue in nursing. With stroke being a leading cause of disability worldwide, it is essential that the impact of the stroke survivor's physical disability be analyzed so interventions can be developed to relieve related caregiver burden. The purpose of this systematic review is to review the existing nursing and allied-health literature aimed at the impact of stroke survivors' physical disability on the presence of care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In previous studies, disease type ( 10 , 61 ) and trajectory ( 63 ) were reported to affect the caregiver burden. In particular, the caregiver burden is high for dementia ( 61 ), stroke ( 12 ), and schizophrenia ( 19 ). In cases of dementia, the caregiver burden differs depending on the type of dementia (Lewy body disease > Alzheimer’s disease) ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, disease type ( 10 , 61 ) and trajectory ( 63 ) were reported to affect the caregiver burden. In particular, the caregiver burden is high for dementia ( 61 ), stroke ( 12 ), and schizophrenia ( 19 ). In cases of dementia, the caregiver burden differs depending on the type of dementia (Lewy body disease > Alzheimer’s disease) ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review study (10), factors related to care burden were classified into three categories: care-recipient-, caregiver-, and society-related factors. Care-recipient factors influencing care burden were physical disability (11)(12)(13), mental dependency (11), and behavioral and psychological symptoms of dementia (13). Caregiver factors were gender (11), age (13)(14)(15), satisfaction with care (16), caring time (10,17,18), duration of caregiving (11), care attitude (19), and stress (6,11).…”
Section: Introductionmentioning
confidence: 99%
“…Nursing implications. Because rehabilitation measures to improve mobility are considered the most effective strategy for stroke patients 24 and mobility is associated with depression, 25 caregiver burden, 26 and adverse outcomes, backward walking speed can guide nurses in developing rehabilitation plans, assessing rehabilitation outcomes, and developing risk intervention strategies in community rehabilitation. The 3MBW is currently a common tool for testing backward walking speed.…”
Section: Discussionmentioning
confidence: 99%
“…troke is the leading cause of disability and death affecting people worldwide. 1,2 Poststroke fatigue (PSF) is one of the most common debilitating and pervasive syndromes after stroke. The prevalence of PSF occurs in up to 72% of stroke survivors.…”
mentioning
confidence: 99%